A Problem None Can Solve Alone: RA21 as Collaborative Effort - O'Neill, Jill (Collaborative librarianship, 2018)
Stakeholders in the information community recognize the challenges surrounding user authentication in the context of licensed information resources. Resource Access in the 21st Century (RA21) is one cross-sector initiative that is intended to reduce those challenges for both academic libraries as well as content and technology providers. Further collaboration by stakeholders may assuage some of the hesitations regarding RA21.